Presumed COL4A3/COL4A4 Missense/Synonymous Variants Induce Aberrant Splicing - Deng, Haiyue; Zhang, Yanqin; Ding, Jie; Wang, Fang (Frontiers in Medicine, 2022)
Background: The incorrect interpretation of missense and synonymous variants can lead to improper molecular diagnosis and subsequent faulty genetic counselling. The aim of this study was to evaluate the pathogenicity of presumed COL4A3/COL4A4 missense and synonymous variants detected by next-generation sequencing to provide evidence for diagnosis and genetic counselling. Methods: Patients’ clinical findings and genetic data were analysed retrospectively. An in vitro minigene assay was conducted to assess the effect of presumed COL4A3/COL4A4 missense and synonymous variants on RNA splicing. Results: Five unclassified COL4A3/COL4A4 variants, which were detected in five of 343 patients with hereditary kidney diseases, were analysed. All of them were predicted to affect splicing by Human Splicing Finder. The presumed COL4A3 missense variant c.4793T>G [p. (Leu1598Arg)] resulted in a loss of alternative full-length transcript during the splicing process. The COL4A3 transcript carried synonymous variant c.765G>A [p. (Thr255Thr)], led to an in-frame deletion of exon 13. Nevertheless, variants c.3566G>A [p. (Gly1189Glu)] in COL4A3 and c.3990G>A [p. (Pro1330Pro)], c.4766C>T [p. (Pro1589Leu)] in COL4A4 exhibited no deleterious effect on splicing. Among the five patients harbouring the abovementioned COL4A3/COL4A4 variants, three patients were genetically diagnosed with autosomal recessive Alport syndrome, one patient was highly suspected of having thin basement membrane nephropathy, and the other patient was clinically diagnosed with Alport syndrome. Conclusions: COL4A3 presumed missense variant p. (Leu1598Arg) and synonymous variant p. (Thr255Thr) affect RNA splicing, which highlights the prime importance of transcript analysis of unclassified exonic sequence variants for better molecular diagnosis and genetic counselling. Meanwhile, the reliability of splicing predictions by Human Splicing Finder for exonic substitutions needs to be improved.